2021
DOI: 10.1021/acsearthspacechem.1c00038
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Oxidative Potential of Organic Aerosol from Heated Cooking Oil

Abstract: Cooking emissions contribute significantly to organic aerosol in urban areas, but the evolution of physicochemical properties and health impacts upon atmospheric aging remain poorly understood. In this study, detailed chemical composition and oxidative potential (OP) of primary organic aerosol (POA) and secondary organic aerosol (SOA) from heated cooking oils (canola, olive, peanut) were characterized. Results from acellular oxidative potential measurements indicate an enhanced OP in photochemically aged cooki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 104 publications
2
18
0
Order By: Relevance
“…Atmospheric aging could also affect PO abundance in aerosols. Enhanced PO content was observed in SOA from α-pinene, naphthalene, and cooking emissions during atmospheric photochemical aging. ,, …”
Section: Observations Of Pos In Laboratory and Field Studiesmentioning
confidence: 97%
“…Atmospheric aging could also affect PO abundance in aerosols. Enhanced PO content was observed in SOA from α-pinene, naphthalene, and cooking emissions during atmospheric photochemical aging. ,, …”
Section: Observations Of Pos In Laboratory and Field Studiesmentioning
confidence: 97%
“…This is in line with a very recent study showing that the total ROS production from cooking SOA can be enhanced substantially through atmospheric aging, coinciding with the elevation in peroxide contents. 59 Isoprene SOA is measured to have high peroxide content (∼97%) compared to Surratt et al 60 (∼61%, from a Teflon chamber); this difference may be due to excess RO 2 • chemistry in the PAM reactor, inducing more production of peroxides through termination steps such as RO 2…”
mentioning
confidence: 89%
“…114 Katragadda et al 115 have shown that emissions from cooking methods such as deep frying at temperatures above smoking point of an oil, can contain exceeding levels of OE. In the recent work of Wang et al, 48 iodometry was applied to quantify total peroxide content in primary organic aerosols emitted from heating of different edible oils. In this case, it is possible that the demonstrated OE interference can lead to inaccurate estimations of total peroxide content.…”
Section: Discussionmentioning
confidence: 99%
“…This is a standard method employed for measuring rancidity in oil and toxicity in lipids. , Despite the experimental variations between the PV method employed for lipid peroxides and iodometry for aerosol-bound peroxides, the principal chemistry is the same as outlined by reactions (1) and (2) in Scheme . Today, iodometry is still widely employed in a number of research fields, with its recent applications including peroxide determination in vegetable oils, , lipid extracts from meat, and outdoor and indoor environments. , …”
Section: Introductionmentioning
confidence: 99%